Peningkatan Hasil Belajar PJOK Materi Permainan Bola Voli dengan Menggunakan Metode Bermain Berpasangan - Imanuddin, Imanuddin (TSAQOFAH, 2022)
The type of research being conducted was classroom action research (PTK) where the target was fifth grade students at SD 2 Rumbuk Timur. The purpose of this classroom action research (PTK) was to find out how far PJOK students' learning outcomes had increased by implementing pair games. class action (CAR) was carried out in 2 cycles, from the results of the actions taken it was proven to be able to improve student learning outcomes by achieving the specified classical completeness of 85%. Classical completeness 70% obtained in the first cycle, can be increased in the second cycle to 100%. In terms of student activity there was also an increase, namely in cycle I, the moderately active category was obtained, increasing to the active category. The results of this action research show that the application of Using Pairs Games can improve student learning outcomes in PJOK lessons with completeness reaching 100%.